2005
DOI: 10.2527/2005.8361312x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets containing linoleic acid- or oleic acid-rich oils on ruminal fermentation and nutrient digestibility, and performance and fatty acid composition of adipose and muscle tissues of finishing cattle1

Abstract: Two trials were conducted to determine the effect of linoleic acid- or oleic acid-rich safflower oil on ruminal fermentation, nutrient digestion, feedlot performance, carcass characteristics, and fatty acid composition of adipose and muscle tissues of beef cattle. In both trials, cattle were fed a finishing diet based on barley grain, wheat silage, and alfalfa hay. Oils were fed at 5% of dietary DM. In a metabolism trial, four ruminally and duodenally cannulated Angus crossbred steers were subjected to linolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 43 publications
6
41
2
9
Order By: Relevance
“…Linoleic acid is toxic to ruminal protozoa and previous research has shown a consistent decrease in protozoal counts in vivo (Sutton et al, 1983;Hristov et al, 2004) and in vitro (Newbold and Chamberlain, 1988). Hristov et al (2005) reported in vitro data showing 48%, 88% and 100% eradication of ruminal protozoa with inclusion of 0.25%, 0.5% and 1% linoleic acid, respectively, in the incubation media. Another study showed that oleic acid at 0.25%, 0.5% and 1% decreased protozoal counts by 26%, 45% and 78%, respectively (Hristov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid is toxic to ruminal protozoa and previous research has shown a consistent decrease in protozoal counts in vivo (Sutton et al, 1983;Hristov et al, 2004) and in vitro (Newbold and Chamberlain, 1988). Hristov et al (2005) reported in vitro data showing 48%, 88% and 100% eradication of ruminal protozoa with inclusion of 0.25%, 0.5% and 1% linoleic acid, respectively, in the incubation media. Another study showed that oleic acid at 0.25%, 0.5% and 1% decreased protozoal counts by 26%, 45% and 78%, respectively (Hristov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in recent years there is increased research interest in the possible modification of this profile, aiming to increase the content of fatty acids considered beneficial for the consumer health. Research has shown that ruminant meat fatty acid profile can be influenced by different rations [34], such as the inclusion of rich PUFA sources in cattle diets [35]. Dietary lipids are subjected to lipolysis by rumen bacteria, which then hydrogenate and isomerize the PUFA included in the feed to more saturated end products [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Pérez Alba et al (1997) and Gallardo et al (2014) reported a drastic increase in the content of trans-18:1 and t 11-18:1 isomers, respectively, in dairy sheep that were also offered calcium soap of olive oil. However, Hristov et al (2005), in a study comparing sunflower oil rich in linoleic acid (76.5% linoleic acid) and sunflower oil rich in oleic acid (76.5% oleic acid) in concentrate lot steers, found no differences in the content of t 11-18:1 or c 9,t 11-18:2. The observed increase in the content of trans-18:1 isomers when supplementing with oils rich in oleic acid could be due to the fact that oleic acid can interfere with the biohydrogenation of linoleic acid, leading to an accumulation of trans-18:1 (Mosley et al, 2002).…”
Section: Meat Qualitymentioning
confidence: 95%